Networked discontent: The anatomy of protest campaigns in social media - González-Bailón, S; Wang, N (Elsevier, 2015)
We analyze the communication network that emerged in social media around an international protest campaign launched in May 2012. Applying insights from network science and the theory of brokerage, we examine the cohesion of the network with community detection methods, and identify the users that spanned structural holes, creating bridges for potential information diffusion. We also analyze actual message exchange to assess how the network was used to facilitate the transmission of information. Our findings provide evidence of fragmentation in online communication dynamics, and of a distribution of brokerage opportunities that was both uneven and underexploited. We use these findings to assess recent theoretical claims about political protests in the digital age.